MADRASAH: PERKEMBANGAN, MODERNISASI DAN IMPLIKASINYA - Masadah Ma'sadah (Al Hikmah: Jurnal Studi Keislaman, 2011)
The Madrasah is one form of Islamic educational institutions, early development, the madrasa is an independent educational institution, after Indonesia's independence, the government set a madrassa as a model and source of national education under the 1945 Constitution, in 1975, issued a joint decree (SKB) three of the Minister, the Minister of Education and Culture, Ministry of Interior and Minister of Religious Affairs of the Madrasah Quality Improvement which aims to madrasas obtain the same position with the public schools in the national education system. As a follow-up is the letter of the joint decision between the Minister of Education and Culture, Religious Affairs Minister No. 9299/U/1984 No. 45 of the Public School Curriculum Standardization settings and Madrasah curriculum. After the specified Law number 20 of 2003 on national education systems as a replacement and refinement of the previous Act VI of chapter 17 and chapter 18, the position of madrasas grew stronger as expressly referred to its position parallel to the public schools of equal rank. The position is formally defined as a product of equal educational policy of government, certainly not fully able to boost the prestige of academic madrasas until today as the emergence of opinion that the madrassas are second class. Therefore madrasas must reorganize itself to catch up in the mastery of general knowledge in public schools while providing adequate attention to the mastery of religious knowledge.